Assessing The Influence of Digital Entrepreneurial Ecosystem on Competitive Advantage: Insights From Women Digital Entrepreneurs - Purbasari, Ratih; Mahira, Siti Alyqha; Suwandi, Imam (Indonesian Journal of Business and Entrepreneurship, 2025)
Background: The growing importance of the digital entrepreneurial ecosystem (DEE) for business competitiveness, particularly among women digital entrepreneurs, was increasingly recognized. Research suggested that supportive ecosystems offered vital resources and networks. This study investigated this relationship specifically among women digital entrepreneurs in West Java.Purpose: To explain the influence of the DEE on the competitive advantages of women digital entrepreneurs in West Java.Design/methodology/approach: A quantitative method using regression analysis with Smart PLS 4 was applied to data from 135 women digital entrepreneurs in West Java.Findings/Result: The DEE positively and significantly influences the competitive advantages of women digital entrepreneurs in West Java. The relationship is strong and stable, indicating a reliable impact of the digital ecosystem on competitiveness.Conclusion: The DEE is a key driver of competitive advantages for women digital entrepreneurs in West Java, providing essential resources and opportunities. This study offers empirical evidence supporting the relevance of the DEE in fostering competitiveness and contributes to the theoretical understanding.Originality/value (State of the art): This study provides specific empirical evidence on the DEE's influence on the competitive advantages of women digital entrepreneurs in West Java. It offers a theoretical framework and practical insights for leveraging digital network. Future research should explore the role of entrepreneurial communities in this dynamic. Keywords: women digital entrepreneur, digital entrepreneurial ecosystem, competitive advantage, digital entrepreneur